2018
DOI: 10.1016/j.ymthe.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

PiggyBac-Engineered T Cells Expressing CD19-Specific CARs that Lack IgG1 Fc Spacers Have Potent Activity against B-ALL Xenografts

Abstract: Clinical trials of CD19-specific chimeric antigen receptor (CAR19) T cells have demonstrated remarkable efficacy against relapsed and refractory B cell malignancies. The piggyBac transposon system offers a less complex and more economical means for generating CAR19 T cells compared to viral vectors. We have previously optimized a protocol for the generation of CAR19 T cells using the piggyBac system, but we found that CAR19 T cells had poor in vivo efficacy and persistence, probably due to deleterious FcγR int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…This increased the separation of these elements from <100 bp to approximately 230 bp. Because our previous work identified CAR19h28TM41BBz as our most effective construct, 22 this CAR was used for evaluation of the new dbDNA configuration. PBMCs were coelectroporated with piggyBac transposase (plasmid or dbDNA) and CAR19h28TM41BBz-transposon (plasmid or larger dbDNA), such that all plasmid and dbDNA pairs were evaluated.…”
Section: Car Is Stably Expressed From Transposon Dbdna With Longer Sementioning
confidence: 99%
See 1 more Smart Citation
“…This increased the separation of these elements from <100 bp to approximately 230 bp. Because our previous work identified CAR19h28TM41BBz as our most effective construct, 22 this CAR was used for evaluation of the new dbDNA configuration. PBMCs were coelectroporated with piggyBac transposase (plasmid or dbDNA) and CAR19h28TM41BBz-transposon (plasmid or larger dbDNA), such that all plasmid and dbDNA pairs were evaluated.…”
Section: Car Is Stably Expressed From Transposon Dbdna With Longer Sementioning
confidence: 99%
“…When expressed, the transposase excises the transposon from the second plasmid and integrates it into the cellular genome. We have previously described a simple and inexpensive method for generating CAR T cells using the piggyBac system 21 and demonstrated that CAR19 T cells produced in this manner are capable of eradicating B cell acute lymphoblastic leukemia (B-ALL) xenografts in vivo 22 and CD19 + malignancies in humans. 23 Plasmids can be produced inexpensively at large scale, but their reliance on bacteria for amplification has several disadvantages for clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Transduction with a viral vector encoding a polycistronic construct of both α and β chains of the transgenic TCR separated by a ribosomal skip motif, such [71][72][73] and nanoparticles, 74 are also in development.…”
Section: General Considerations In Developing Tcr Immunotherapymentioning
confidence: 99%
“…However, clinical grade retroviral vectors are costly to produce and can be generated at only a few facilities. The work in this issue of Molecular Theapy by Bishop et al 1 reveals that non-viral piggyBac transposon-generated CD19-specific chimeric antigen receptor (CAR) T cells have excellent in vivo efficacy in the setting of patient derived CD19+ B-acute lymphoblastic leukemia (ALL) in an animal model. Although piggyBac transposon-generated CAR T cells had previously demonstrated in vitro efficacy, 2-4 sustained activity in vivo had not been reported until now.…”
mentioning
confidence: 99%
“…Therefore, a human immune system and malignancy is not fully recapitulated. Nonetheless, the study by Bishop et al 1 is an important step towards clinical testing and application.…”
mentioning
confidence: 99%